Forecasting Gold Prices in Indonesia using Support Vector Regression with the Grid Search Algorithm - Nonong Amalita; Dodi Vionanda; Zamahsary Martha; Nindi Syahfitrri (Departemen Statistika Universitas Negeri Padang, 2024)
Investment is an effort to increase economic growth in Indonesia. A popular investment in the community is gold investment. The value of gold investments tends to increase but is not immune from price fluctuations, therefore it is important to forecast the price of gold in Indonesia. The method that can be used to make this forecast is Support Vector Regression (SVR). SVR is a method that looks for a function that has a deviation of no more than ε to get the target value from all training data. The best SVR model with a linear kernel was obtained from a combination of parameters C=0,0625 and ε=0,001 with a RMSE value of 0,19734 and a value of 0,974112. So, the SVR method is appropriate to use for forecasting gold prices in Indonesia.